CAFF Progress report to SAOs, Report from CAFF biennial 2011. - Conservation of Arctic Flora and Fauna (CAFF) (CAFF International Secretariat, 2011)
Arctic Council working group Conservation of Arctic Flora and Fauna (CAFF)s progress report, presented at the Arctic Council's Senior Arctic Officials meeting in Copenhagen, Denmark, March 16-17 2011. This report constitutes an overview of CAFF work since the previous SAO meeting and a summary of the key issues facing Arctic Biodiversity as discussed at the CAFF Biennial. The CAFF Biennial was held at the Hof Cultural Centre, Akureyri, Iceland on 1– 3rd February 2011. It was chaired by Aevar Petersen from Iceland with Natalia Vavilova from Russia as the vice-chair. The meeting was opened by the Icelandic Minister of the Environment who gave a speech stressing the importance of CAFFs work and Iceland’s commitment to hosting the CAFF Secretariat.